Is Conflict Adaptation an Illusion? - James R Schmidt (Frontiers Research Topics, 2015)
Conflict adaptation theory is one of the most popular theories in cognitive psychology. The theory argues that participants strategically modulate attention away from distracting stimulus features in response to conflict. Although results with proportion congruent, sequential congruency, and similar paradigms seem consistent with the conflict adaptation view, some researchers have expressed scepticism. The paradigms used in the study of conflict adaptation require the manipulation of stimulus frequencies, sequential dependencies, time-on-task regularities, and various other task regularities that introduce the potential for learning of conflict-unrelated information. This results in the unintentional confounding of measures of conflict adaptation with simpler learning and memory biases. There are also alternative accounts which propose that attentional adaptation does occur, but via different mechanisms, such as valence, expectancy, or effort. A significant (and often heated) debate remains surrounding the question of whether conflict adaptation exists independent of these alternative mechanisms of action. The aim of this Research Topic is to provide a forum for current directions in this area, considering perspectives from all sides of the debate.